2013
DOI: 10.1159/000356641
|View full text |Cite
|
Sign up to set email alerts
|

Pendrin, a Novel Transcriptional Target of the Uroguanylin System

Abstract: Guanylin (GN) and uroguanylin (UGN) are low-molecular-weight peptide hormones produced mainly in the intestinal mucosa in response to oral salt load. GN and UGN (guanylin peptides) induce secretion of electrolytes and water in both intestine and kidney. Thought to act as “intestinal natriuretic factors”, GN and UGN modulate renal salt secretion by both endocrine mechanisms (linking the digestive system and kidney) and paracrine/autocrine (intrarenal) mechanisms. The cellular function of GN and UGN in intestine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 124 publications
0
3
0
Order By: Relevance
“…Surprisingly, the prevalence of PDS-aAb was only slightly higher in thyroid patients than in controls, indicating that AITD may not be the relevant disease for autoimmunity to PDS. Studies in other diseases potentially related to PDS expression are needed next to elucidate a possible role of PDS-aAb in conditions other than AITD, like diseases of the lungs (28), esophagus (29), placenta (30), kidney (31) or in rhinosinusitis (32).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, the prevalence of PDS-aAb was only slightly higher in thyroid patients than in controls, indicating that AITD may not be the relevant disease for autoimmunity to PDS. Studies in other diseases potentially related to PDS expression are needed next to elucidate a possible role of PDS-aAb in conditions other than AITD, like diseases of the lungs (28), esophagus (29), placenta (30), kidney (31) or in rhinosinusitis (32).…”
Section: Discussionmentioning
confidence: 99%
“…This sensitivity was associated with a rise in cGMP levels in urine and an upregulation of the GC-C receptor and downregulation of guanylate cyclase A (GC-A) receptors in kidney seen by real time PCR [15]. The guanylin family signaling pathways in the kidney has become the subject of numerous recent research due to its great importance in this process [7,15,28,39]. Therefore, the current study demonstrates that uroguanylin is more important than urodilatin in excreting sodium after a chronic salt overload diet.…”
Section: Discussionmentioning
confidence: 99%
“…In the inner ear, pendrin helps maintain Cl − and HCO 3 − homeostasis, which is crucial for normal hearing and for the development of bony structures such as the cochlea and the vestibular aqueduct [ 71 ]. In the thyroid gland, pendrin contributes I − to the follicle for thyroxine biosynthesis [ 72 ], and in the cortical collecting duct the transporter is implicated in Cl − reabsorption through functional coupling with the epithelial Na + channel ENaC and the Na + -dependent Cl − /HCO 3 − exchanger NDCBE/SLC4A8 [ 73 ]. Most interestingly, it has been shown that in the bronchial epithelium pendrin mediates an increase in Cl − /SCN − exchange in response to IL-4 stimulation [ 74 ] to provide SCN − substrate to lactoperoxidase for the synthesis of hypothiocyanite (OSCN − ), a molecule with antimicrobial properties [ 75 ], and this underscores the emerging role of pendrin in innate airway defense mechanisms ( Figure 5 ).…”
Section: Slc26: An Ancient Family With Unexpected New Rolesmentioning
confidence: 99%